2013
DOI: 10.1105/tpc.112.107409
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Signal Peptide Binding and Oligomer Contact Sites of the Core Subunit of the Pea Twin Arginine Protein Translocase

Abstract: Twin arginine translocation (Tat) systems of thylakoid and bacterial membranes transport folded proteins using the proton gradient as the sole energy source. Tat substrates have hydrophobic signal peptides with an essential twin arginine (RR) recognition motif. The multispanning cpTatC plays a central role in Tat operation: It binds the signal peptide, directs translocase assembly, and may facilitate translocation. An in vitro assay with pea (Pisum sativum) chloroplasts was developed to conduct mutagenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 55 publications
(105 reference statements)
15
60
0
Order By: Relevance
“…This finding is consistent with previous observations that these two proteins copurify in detergent solution as a large TatBC complex and that the size and composition of the complex are not significantly altered by substrate binding (19,22,45,49,50). It is also consistent with the observation that TatBC complexes do not exhibit the exchange of TatC subunits that would be expected if TatC undergoes assembly cycles (23). We find that the TatB protein has a lower oligomer state if TatC is absent but that TatC oligomerization is independent of TatB.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with previous observations that these two proteins copurify in detergent solution as a large TatBC complex and that the size and composition of the complex are not significantly altered by substrate binding (19,22,45,49,50). It is also consistent with the observation that TatBC complexes do not exhibit the exchange of TatC subunits that would be expected if TatC undergoes assembly cycles (23). We find that the TatB protein has a lower oligomer state if TatC is absent but that TatC oligomerization is independent of TatB.…”
Section: Discussionsupporting
confidence: 82%
“…Tat-signal peptides are recognized at the membrane by a TatBC receptor complex (18)(19)(20)(21)(22)(23). Substrate protein binding to TatBC causes a PMF-dependent recruitment of TatA (and presumably TatE) to assemble the active translocation site (18,24).…”
mentioning
confidence: 99%
“…3A shows residues of chloroplast TatC (colored orange and red) that, when mutated to alanine, impair signal peptide binding. Residues colored red (glutamate) are thought to coordinate the arginine guanidinium groups; residues colored green direct disulfide cross-linking to RR proximal residues of the signal peptide (56). Complementary evidence also suggests that signal peptide H domain uniformly binds to the TatB TM, which is simultaneously associated with TatC TM5.…”
Section: Substratementioning
confidence: 91%
“…The TatB and TatC proteins form a multivalent complex that binds Tat substrates through their twin arginine signal peptides (18)(19)(20). Numerous experiments have shown that the TatC component recognizes the twin arginine motif (21)(22)(23)(24)(25)(26), whereas TatB is close to the signal peptide h-region (27,28). Signal peptides have been shown to penetrate deeply into the TatBC complex (29) and, in thylakoids at least, this deep-binding mode may be modulated by the transmembrane proton electrochemical gradient (PMF) (30).…”
mentioning
confidence: 99%